Analisis Hukum Ekonomi Syariah terhadap Akad Gadhoh dan Bagi Hasil dalam Usaha Peternakan Sapi: Studi Kasus Masyarakat Tiyuh Gilang Tunggal Makarta - Anton Sujarwo (Journal Tafkirul Iqtishodiyyah, 2025)
This study examines the implementation of the gadhoh livestock system in Tiyuh Gilang Tunggal Makarta, Lambu Kibang District, Tulang Bawang Barat Regency, where livestock cooperation between capital owners and caretakers has long been practiced as part of local economic traditions. In this system, the capital owner entrusts cattle to a caretaker who is responsible for all livestock needs, and profit sharing is conducted when the cattle give birth or are sold at maturity, commonly referred to as maro anak for female cattle and maro bathi for male cattle. Although historically successful, the number of farmers participating in the gadhoh system has recently declined. This study aims to describe the operational mechanism of the cattle gadhoh system and analyze it through the lens of Sharia Economic Law. Using a qualitative descriptive approach based on field research, the findings reveal that the gadhoh system is perceived not merely as a profit-oriented cooperation, but also as a means of strengthening social ties and maintaining local wisdom. The system remains relevant because it offers investment opportunities for capital owners and provides additional income for livestock caretakers. In some cases, caretakers eventually establish independent livestock businesses due to herd growth, rather than dissatisfaction with the profit-sharing scheme. From a Sharia Economic Law perspective, the gadhoh system reflects several key principles, including profit sharing (mudarabah), fairness in distribution, shared risk, and ethical conduct (nubuwwah). Overall, the gadhoh cooperation model has the potential to serve as a strategic approach for community-based livestock development in Indonesia.